Propensity-Matched Comparisons of Clinical Outcomes After Transapical or Transfemoral Transcatheter Aortic Valve Replacement. Issue 22 (2nd June 2015) - Blackstone, Eugene H.; Suri, Rakesh M.; Rajeswaran, Jeevanantham; Babaliaros, Vasilis; Douglas, Pamela S.; Fearon, William F.; Miller, D. Craig; Hahn, Rebecca T.; Kapadia, Samir; Kirtane, Ajay J.; Kodali, Susheel K.; Mack, Michael; et al.
<x xml:space="preserve">Abstract</x> Background— The higher risk of adverse outcomes after transapical (TA) versus transfemoral (TF) transcatheter aortic valve replacement (TAVR) could be attributable to TA-TAVR being an open surgical procedure or to clinical differences between TA- and TF-TAVR patients. We compared outcomes after neutralizing patient differences using propensity score matching. Methods and Results— From April 2007 to February 2012, 1100 Placement of Aortic Transcatheter Valves (PARTNER)-I patients underwent TA-TAVR and 1521 underwent TF-TAVR with Edwards SAPIEN balloon-expandable bioprostheses. Propensity matching based on 111 preprocedural variables, exclusive of femoral access morphology, identified 501 well-matched patient pairs (46% of possible matches), 95% of whom had peripheral arterial disease. Matched TA-TAVR patients experienced more adverse procedural events, longer length of stay (5 versus 8 days; P<0.0001), and slower recovery (New York Heart Association class I, 31% versus 38% at 30 days, equalizing by 6 months at 51% versus 47%); stroke risk was similar (3.4% versus 3.3% at 30 days and 6.0% versus 6.7% at 3 years); mortality was elevated for the first 6 postprocedural months (19% versus 12%; P=0.01); but aortic regurgitation was less (34% versus 52% mild and 8.9% versus 12% moderate to severe at discharge, P=0.001; 36% versus 50% mild and 10% versus 15% moderate to severe at 6 months, P<0.0001). Conclusions— The likelihood of adverse periprocedural events and prolonged recovery is greater after TA-TAVR than TF-TAVR in vasculopathic patients after accounting for differences in cardiovascular risk factors, although stroke risk is equivalent and aortic regurgitation is less. As smaller delivery systems permit TF-TAVR in many of these patients, we recommend a TF-first access strategy for TAVR when anatomically feasible. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00530894.